Warehouse management and inventory control - Price, P.M (Access Education, 2015)
Warehouse Management and Inventory Control is a fun, accessible, and comprehensive first look at the world of warehouses and inventory that can easily be used as a textbook in the college, community college, and high school setting. It is written in an engaging, fun, and accessible style and every chapter includes interesting case studies or exercises. It is also a useful reference for those in the business world new to warehouse management and inventory control.